Maktabda informatika va axborot texnologiyalarini o‘qitishda sun’iy intellekt texnologiyalaridan foydalanish - Raxmatov Tursunpo’lot Raupovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
It is difficult to imagine our present day without the Internet and information technologies. Therefore, in order to increase students' interest in lessons in every aspect, especially in school classes, every subject teacher should use the achievements of information technology in his specialty. In recent years, the development of artificial intelligence technologies has led to the emergence of new approaches in all fields. In particular, the experience of using elements of artificial intelligence is being accumulated in the field of education and teaching technologies.